2021
DOI: 10.1007/s11136-021-02982-3
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and heterogeneity in health-related quality of life: findings based on a large sample of cross-sectional EQ-5D-5L data from the Swedish general population

Abstract: Purpose This study aimed to investigate inequality and heterogeneity in health-related quality of life (HRQoL) and to provide EQ-5D-5L population reference data for Sweden. Methods Based on a large Swedish population-based survey, 25,867 respondents aged 30‒104 years, HRQoL is described by sex, age, education, income, economic activity, health-related behaviours, self-reported diseases and conditions. Results are presented by EQ-5D-5L dimensions, responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
4
21
1
1
Order By: Relevance
“…Our results are in line with previous findings using the one-dimension self-rated health question (4) showing variation in inequalities in health associated with socioeconomic status across European countries. The successful application of the EQ-5D (both 3L or 5L) in socio-demographic analyses in selected countries and regions were also confirmed by several other recent studies (36)(37)(38)(39), and in vulnerable groups like homeless persons (40). Specifically, Sronk et al showed that among three European countries the EQ-5D-5L was able to detect education level related inequalities in health, however, differences varied across countries and some of the impact was canceled out when controlling for chronic conditions and ability to work.…”
Section: Discussionsupporting
confidence: 73%
“…Our results are in line with previous findings using the one-dimension self-rated health question (4) showing variation in inequalities in health associated with socioeconomic status across European countries. The successful application of the EQ-5D (both 3L or 5L) in socio-demographic analyses in selected countries and regions were also confirmed by several other recent studies (36)(37)(38)(39), and in vulnerable groups like homeless persons (40). Specifically, Sronk et al showed that among three European countries the EQ-5D-5L was able to detect education level related inequalities in health, however, differences varied across countries and some of the impact was canceled out when controlling for chronic conditions and ability to work.…”
Section: Discussionsupporting
confidence: 73%
“…EQ-5D-5L has been used to evaluate health inequality in other studies. Mean index values, EQ VAS scores, 'domain scores' (the mean level of reported problems from 1 to 5 on the five dimensions), and level sum scores (the mean of sum of the five levels for a population) have been used to compare socioeconomic and demographic groups in various countries in Europe and Asia [6][7][8][9]. Ordinary least squares regression models have been used to estimate coefficients for the effect of demographic and socioeconomic indicators on EQ VAS scores.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinary least squares regression models have been used to estimate coefficients for the effect of demographic and socioeconomic indicators on EQ VAS scores. Logit and tobit regression models have been used to estimate odds ratios for reporting problems on the five dimensions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a Swedish population-based study, including 25 867 adults between 30 and 103 years, 29 the CA survivors with good cerebral performance reported equal median scores on the EQ VAS as persons with low education level, the group with poorest health status in the general population. However, survivors with moderate cerebral disability reported in average 15 points lower on Open access the EQ VAS compared with persons with low education level in the general population.…”
Section: Discussionmentioning
confidence: 60%